The Enzymatic Process of Macroalgae for Conversion into High-tech Bioproducts - Han, JooHee; Jo, YeWon; Sun, Habin; Lee, EunSeo; Chae, UnJung; Han, Sung Ok; Kim, Jong Hun; Hyeon, Jeong Eun (Biotechnology and bioprocess engineering, 2023)
Macroalgae are one of various groups of multicellular algae include some types of Rhodophyta (red), Phaeophyta (brown), and Chlorophyta (green) macroalgae. They are now a source for biorefineries, as they contribute to energy production as biomass. Algae are worth noting because of their high content in compounds with separate biological activities, including agar, agarose, and carrageenan in red algae; alginates, laminarin, and fucoidan in brown algae; and ulvan, sulfated galactans, and xylans in green algae. Skeletal polysaccharides of red algae are composed of cellulose 1,β-1,3-mannan and β-1,4-acrylic acid. More than half of the dry weight of brown algae is made up of the polysaccharides alginate, laminarin, and fucoidan, and this percentage can even exceed 70% in some species. They are converted to monosaccharides that can be easily used by using polysaccharide hydrolysis enzymes. This process has the potential to maximize biofuel yields. Compared with the enzymatic depolymerization of brown and red algae polysaccharides, the depolymerization of green algae polysaccharides has been less extensively investigated. However, the use of ulvan lyase is very promising because it can degrade ulvan with good specificity, high efficiency, and mild reaction conditions, and it can well maintain the rare sugar structure properties of ulvan. The depolymerization process of macroalgae by chemical hydrolysis requires high cost, causes environmental pollution, and has limited use due to problems such as low yield. Therefore, an environmentally friendly, energy efficient and economical enzymatic depolymerization process of macroalgae using degrading enzyme will be needed.